2013
DOI: 10.1074/mcp.m113.029272
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Detergent-resistant Membrane Microdomains in Trophozoite Blood Stage of the Human Malaria Parasite Plasmodium falciparum

Abstract: Intracellular pathogens contribute to a significant proportion of infectious diseases worldwide. The successful strategy of evading the immune system by hiding inside host cells is common to all the microorganism classes, which exploit membrane microdomains, enriched in cholesterol and sphingolipids, to invade and colonize the host cell. These assemblies, with distinct biochemical properties, can be isolated by means of flotation in sucrose density gradient centrifugation because they are insoluble in nonionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
(64 reference statements)
2
20
0
Order By: Relevance
“…While the two samples were separately analysed by MS, nowhere in the entire study it is indicated if PfEMP1 was detected from the soluble fraction or the membrane fraction. Another study by Yam et al in 2013 described proteomics analysis of total detergent resistant membrane microdomains in the trophozoite stage and this study also does not report detection of PfEMP1 by MS . The above data from published literature suggests that the detection of PfEMP1 by mass spectrometric approaches has been possible only from soluble fractions of the parasite during its transport and not from detergent resistant membranes where it is ultimately located.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…While the two samples were separately analysed by MS, nowhere in the entire study it is indicated if PfEMP1 was detected from the soluble fraction or the membrane fraction. Another study by Yam et al in 2013 described proteomics analysis of total detergent resistant membrane microdomains in the trophozoite stage and this study also does not report detection of PfEMP1 by MS . The above data from published literature suggests that the detection of PfEMP1 by mass spectrometric approaches has been possible only from soluble fractions of the parasite during its transport and not from detergent resistant membranes where it is ultimately located.…”
Section: Discussionmentioning
confidence: 71%
“…PfEMP1, the chief cytoadherent protein known to be present on the detergent‐resistant membranes (DRMs) of infected erythrocytes, was not detectable in our proteomics analysis. A detailed analysis of existing literature on proteomics studies in the parasite reveals that till date PfEMP1 has been determined through MS approaches only in the soluble fractions of the parasite and never in DRMs . This is in spite of overwhelming evidences from literature that have established beyond doubt that PfEMP1 proteins are integral components of knobs which are present in DRMs.…”
Section: Discussionmentioning
confidence: 99%
“…to deplete it of rafts, rather than to satisfy a need in cholesterol for the parasite. Trophozoites recruit cholesterol from lipid rafts of red blood cells disrupting signalling and possibly affecting immune response toward infected cells [37]. …”
Section: Pathogens Target Cellular Cholesterol Metabolismmentioning
confidence: 99%
“…Sample Preparation for Proteomic Analysis-Proteins extracted from DRM fractions 2-8 were loaded on SDS-PAGE (home-made 5% stacking-12% resolving bis-tris-PAGE) and run just to allow the pro-tein marker (BenchMark™ Pre-Stained Protein Ladder, Invitrogen, Carlsbad, CA) to enter the resolving gel. After Coomassie Staining (Novex, Colloidal Blue Staining gel, Invitrogen) unresolved bands were excised and in-gel tryptic digestion was performed as already described (16) with slight modifications. Briefly, gel slices were destained by washings in acetonitrile (ACN)/50 mM NH4CO3 (1:1), treated with 10 mM DTT (40 min at 56°C) and 55 mM iodoacetamide (30 min in the dark at RT) to reduce and alkylate cysteines, shrunken with ACN and rehydrated for 40 min on ice with a solution of 12,5 ng/l trypsin (Promega, Madison, WI) in 50 mM NH 4 CO 3 and protein digestion was carried out overnight at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on Plasmodium asexual blood stages indicated that CH-rich membrane microdomains participate to various biological processes, such as protein sorting/trafficking, host cell invasion, organelle biogenesis and membrane remodeling with a key function in parasite virulence and pathogenesis (13)(14)(15)(16). A specific role of these assemblies in sexual stages has not been investigated so far.…”
mentioning
confidence: 99%